PEMBERDAYAKAN PETANI DALAM PENCIPTAAN NILAI TAMBAH PADA KOMODITAS LADA SEBAGAI UPAYA PENINGKATAN KESEJAHTERAAN - Henri; Novyandra Ilham Bahtera; Arthur M. Farhaby (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2021)
Abstract Pepper farmers in Bangka Belitung are currently facing various challenges and obstacles when the economic conditions are getting more difficult. The local government has provided many programs so that this problem can be resolved including the provision of free seeds, warehouse receipt systems and pest and disease control. However, the program has not been able to be utilized optimally by pepper farmers. This community empowerment program is here to provide knowledge strengthening in utilizing programs from the government as an effort to improve the welfare of pepper farmers and the general public. Therefore, this program offers a solution in the form of community empowerment, especially for pepper farmers to strengthen the capacity of human resources at Gapoktan institutions in managerial terms such as strengthening the function of the organizational structure and detailing the duties and responsibilities of members in the organization. In addition, this program can empower farmers in creating added value for pepper commodities that can provide social and financial benefits to beneficiaries. This program is able to contribute to reducing the problems faced by pepper farmers. Abstrak Petani lada di Bangka Belitung saat ini menghadapi berbagai tantangan dan kendala disaat kondisi perekenomian semakin sulit. Pemerintah daerah telah memberikan banyak program agar masalah ini dapat teratasi diantaranya pemberian benih gratis, sistem resi gudang dan pengendalian hama dan penyakit. Meskipun demikian, progam tersebut masih belum mampu dimanfaatkan oleh petani lada secara optimal. Program pemberdayaan masyarakat ini hadir untuk memberikan penguatan pengetahuan dalam memanfaatkan program dari pemerintah sebagai upaya meningkatkan kesejahteraan petani lada dan masyarakat umumnya. Oleh sebab itu, program ini menawarkan solusi berupa pemberdayaan masyarakat khususnya kepada petani lada untuk menguatkan kapasitas sumber daya manusia pada lembaga gapoktan dalam hal manajerial seperti penguatan fungsi struktur organisasi serta perincian tugas dan tanggung jawab anggota dalam organisasi. Selain itu, program ini dapat memberdayakan petani dalam penciptaan nilai tambah pada komoditas lada yang dapat memberikan keuntungan sosial dan finansial kepada penerima manfaat. Program ini mampu memberikan sumbangsih kepada pengurangan masalah yang dihadapi oleh petani lada.